Collateral, relationship lending and financial distress: An empirical study on financial contracting - Ralf Elsas; Jan Pieter Krahnen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
This paper analyses the role of collateral in loan contracting when companies are financed by multiple bank lenders and relationship lending can be present. We conjecture and empirically validate that relationship lenders, who enjoy an informational advantage over arm's-length banks, are more senior to strengthen their bargaining power in future renegotiation if borrower's face financial distress. This deters costly conflicts between lenders and fosters workout decisions by the best informed party. Consistent with our conjecture, we find that relationship lender in general have a higher probability to be collateralized, and a higher degree of collateralization (i.e. seniority). Furthermore, we show that seniority and the status of relationship lending increases the likelihood that a bank invests in a risky workout of distressed borrowers. Both findings support the view that collateral is a strategic instrument intended to influence the bargaining position of banks. Our result further suggest that seniority and relationship lending are complementary to each other.
urn:nbn:de:hebis:30-53001
Keywords: G21; 330; relationship lending; collateral; multiple lending; loan contract design; workouts